2018
DOI: 10.1002/acr.23553
|View full text |Cite
|
Sign up to set email alerts
|

Phenome‐Wide Association Studies Uncover a Novel Association of Increased Atrial Fibrillation in Male Patients With Systemic Lupus Erythematosus

Abstract: Using PheWAS to compare male and female patients with SLE, we identified a novel association of an increased incidence of atrial fibrillation in male patients. SLE disease status was shown to be independently associated with atrial fibrillation, even after adjustment for age, sex, race, and coronary artery disease. These results demonstrate the utility of PheWAS as an EHR-based discovery tool for SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The study was approved by the Vanderbilt University Institutional review board. We used a previously identified systemic lupus erythematosus (SLE) cohort with matched controls by age, race and gender ( Fig 1 ) [ 21 ]. These SLE cases were identified using previously validated and published algorithms with positive predictive values (PPVs) ≥ 90% [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the Vanderbilt University Institutional review board. We used a previously identified systemic lupus erythematosus (SLE) cohort with matched controls by age, race and gender ( Fig 1 ) [ 21 ]. These SLE cases were identified using previously validated and published algorithms with positive predictive values (PPVs) ≥ 90% [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…11 Class I antiarrhythmic agents are not recommended due to frequent cated by elevated norepinephrine levels could play an etiologic role in a wide range of diseases, including SLE. 26 In general, standard medications for SLE (i.e., glucocorticosteroids 27 and anti-malarial drugs 28 ) often caused tachyarrhythmias and QRS prolongation. However, treatment with chloroquine seems to have a protective effect 29 because it reduces the velocity of the action potential of the cells in the conduction system, prolonging the action potential duration and increasing the refractory period of Purkinje fibers.…”
Section: Sarcoidosismentioning
confidence: 99%
“…Atrial fibrillation occurring at young age has been observed in several autoantibody-associated diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and antiphospholipid syndrome [ 66 , 67 , 68 ]. Among the many self-antigens that have been proposed as potential targets of the self-directed immune responses to the heart [ 69 ], heat shock proteins (HSPs) are of special interest, because changes in cardiac HSP60/65 expression have been observed in patients with AF [ 70 , 71 ] and auto-reactivity to HSPs has been observed patients with periodontal disease [ 72 ].…”
Section: Potential Role Of Autoimmunity In Atrial Fibrillationmentioning
confidence: 99%